2021
DOI: 10.3389/fpls.2021.702196
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Functionality of PGR5/PGRL1-Dependent Cyclic Electron Transport in Sustaining Photosynthesis

Abstract: The cyclic electron transport (CET), after the linear electron transport (LET), is another important electron transport pathway during the light reactions of photosynthesis. The proton gradient regulation 5 (PGR5)/PRG5-like photosynthetic phenotype 1 (PGRL1) and the NADH dehydrogenase-like complex pathways are linked to the CET. Recently, the regulation of CET around photosystem I (PSI) has been recognized as crucial for photosynthesis and plant growth. Here, we summarized the main biochemical processes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 109 publications
1
31
0
Order By: Relevance
“…P700 redox was hardly changing, presumably, because its reduction and oxidation were, without the major CET pathway, balanced. Mingzhu Ma et al 80 noted that the PSI remains fully reduced under high light in the pgr5 mutant and our data suggest that this may remain valid even when the light oscillates.…”
Section: Light Modulationsupporting
confidence: 75%
“…P700 redox was hardly changing, presumably, because its reduction and oxidation were, without the major CET pathway, balanced. Mingzhu Ma et al 80 noted that the PSI remains fully reduced under high light in the pgr5 mutant and our data suggest that this may remain valid even when the light oscillates.…”
Section: Light Modulationsupporting
confidence: 75%
“…In addition to NPQ, several alternative electron transfer (AET) routes become active in response to stress in order to prevent the LET chain from overreduction. To maintain an optimal ATP/NADPH ratio for metabolic processes under such conditions, electrons are rerouted from Fd back to the PQ pool potentially via the Proton Gradient Regulation 5 (PGR5)/PGR5‐like photosynthetic phenotype 1 (PGRL1) complex or the NADH dehydrogenase‐like (NDH) complex, thus driving cyclic electron transfer (CET) around PSI and sustaining ATP synthesis (Ma et al, 2021). The membrane‐embedded NDH‐1 complex not only reduces the PQ pool for CET with electrons deriving from NADPH via FNR and Fd (Mulo and Medina, 2017) but also transfers protons into the thylakoid lumen for activation of the ATP synthase (Peltier et al, 2016).…”
Section: The “Solar Panels” Of the Plant Cell—the Light Reactions Of ...mentioning
confidence: 99%
“…Studies have demonstrated the importance of the cyclic electron transport (CET)-dependent proton motive force (pmf) under low light for ATP synthesis ( Walker et al, 2014 ). PGR5/PGRL1 and NDH can mediate CET processes in low light and facilitate CO 2 assimilation by supplying additional ATP ( Ma et al, 2021 ). Studies have also indicated that the PsbQ protein is required for photoautotrophic growth under low-light conditions ( Yi et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%